Aesthetic appreciation: event-related field and time-frequency analyses - Munar, Enric; Nadal, Marcos; Castellanos, Nazareth P.; Flexas, Albert; Maestú, Fernando; Mirasso, Claudio; Cela-Conde, Camilo J. (Frontiers in Human Neuroscience, 2012)
Improvements in neuroimaging methods have afforded significant advances in our knowledge of the cognitive and neural foundations of aesthetic appreciation. We used magnetoencephalography (MEG) to register brain activity during an aesthetic appreciation task. The data were analyzed with Event-Related Field (ERF) and Time-Frequency (TF) procedures. ERFs revealed no significant differences between brain activity related with stimuli rated as “beautiful” and “not-beautiful”. TF analysis showed clear differences between both conditions 400 ms after stimulus onset. In the four frequency bands (theta, alpha, beta and gamma) oscillatory power was significantly greater for stimuli rated as “beautiful” than those regarded as “not-beautiful”. These results are interpreted in the frame of synchronization studies.